Security of seafarers in the maritime labour convention, 2006 ILO (MLC) - D. Raul Garcia Bercedo; Amaia Castaсos Urkullu; Irwin Purnawarman (Актуальні проблеми транспортної медицини, 2011)
In the year 2010 which marks the year of seafarers, Spain has ratified the Maritime
Labour Convention, 2006 of the International Labour Organization. Becoming the first EU
member to ratify.
This important Maritime Labour Convention, also called “super convention”, was
adopted by the 94th (Maritime) Session of the International Labour Conference held in
Geneva in February 2006. To ratify the MLC, 2006, Spain implemented a decision of the
Council of the European Union 2007, which allows member countries to ratify in the interests
of the European Community and invites them to do so before December 31, 2010.
The objectives of this paper are to introduce and analyze the contents of the
Convention in relation to safety and prevention of occupational accidents in the maritime
environment.
To do this will be discussed in the text of the agreement in relation to Rule 4.3 Health
and safety protection and accident prevention which is designed to ensure that the working
environment of seafarers on board ships promotes safety and health at work.
From this analysis conclusions that will ratify the importance of this agreement to
ensure decent working conditions for seafarers. У 2010 році Іспанія ратифікувала конвенцію Міжнародної організації праці про працю в морському судноплавстві 2006 року, ставши першим членом ЄС, який ратифікував цей важливий документ. Конвенція про працю в морському судноплавстві, звана також «супер конвенція», була прийнята 94 й (морської) сесією Міжнародної конференції праці, що відбулася в Женеві в лютому 2006 року.Затвердивши Конвенцію 2006, Іспанія реалізувала рішення Ради Європейського Союзу від 2007 року, яке дозволяє країнам членам ЄС провести ратифікацію в інтересах Європейського співтовариства до 31 грудня 2010 року. Мета цієї роботи - аналіз змісту Конвенції щодо безпеки та запобігання нещасних випадків в морі у зв’язку з правилом 4.3 - здоров’я, забезпечення безпеки та попередження нещасних випадків, що призначені для забезпечення відповідних гідних умов праці моряків на борту суден та сприяють безпеці та гігієні праці. В 2010 году Испания ратифицировала конвенцию Международной организации труда о труде в морском судоходстве 2006 года, став первым членом ЕС, который ратифицировал этот важный документ. Конвенция о труде в морском судоходстве, называемая также «супер конвенция», была принята 94 й (морской) сессией Международной конференции труда, состоявшейся в Женеве в феврале 2006 года. Утвердив Конвенцию 2006, Испания реализовала решение Совета Европейского Союза от 2007 года, которое позволяет странам членам ЕС провести ратификацию в интересах Европейского сообщества до 31 декабря 2010 года. Цель этой работы — анализ содержания Конвенции в отношении безопасности и предотвращения несчастных случаев в море в связи с правилом 4.3 - здоровье, обеспечение безопасности и предупреждение несчастных случаев, который предназначен для обеспечения соответствующих достойных условий труда моряков на борту судов, способствует безопасности и гигиене труда.